Relatório do estágio curricular supervisionado em Medicina Veterinária – área de clínica e cirurgia de pequenos animais - Pereira, Taynara Dias (2018)
The present work describes the activities carried out and monitored by the academic Taynara Dias Pereira, during the Supervised Curricular Internship in Medicine Veterinary, in the area of clinic and surgery of small animals. The internship was carried out during the period from January 8th to April 6th, 2018, at Hospital Veterinário da School of Veterinary and Animal Science, Federal University of Goiás, on Campus Samambaia, in the City of Goiânia-GO. With the guidance of Professor Dr. Paulo de Souza Junior and under the supervision of Veterinary Medicine Dra. Severiana Cândida Mendonça Cunha Carneiro, totaling 480 hours. Activities focused on small animal clinic and surgery area with a total of 75 patients followed up at the clinic, 33 in the surgery sector, 34 in the hospitalization sector and 24 in the urgency and emergency sector. Of these visits, 156 were canine and 10 cats.